Woodland and bog Rein orchids in your pocket : a guide to native Platanthera species of the continental United States and Canada - Brown, Paul Martin (Bur Oak guide., 2010)
Normal.dotm 0 0 1 124 711 The University of Iowa 5 1 873 12.0 0 false 18 pt 18 pt 0 0 false false false /* Style Definitions */ table. MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast